Cancer from Both Sides Now: Combining Personal and Research Perspectives on Survivorship - Blank, Thomas O. (Springer-Verlag, 2009)
Cancer survivorship is increasingly a situation of chronic disease management that needs to be integrated with the context of broader health and well-being. This perspective paper combines personal experiences and a professional research program to address the complexities of long-term management of cancer and integrated care and the importance of psychological distress and psychological growth expressed in diverse pathways of survivorship. The role of age is addressed as partially defining the extent and nature of long-term psychological effects. General internists are in a unique position to play a central role in enabling cancer survivors to integrate the cancer experience into their lives and their overall health and well-being.